(untitled) (Eurasian Medical Research Periodical, 2022)
Collecting 50 patients from different Hospitals, in Iraq. and 15 control groups, where the study aimed at assessing cases of hypertension in smokers, and the study period for data analysis was for a full year, and it was based on statistical analysis programs SPSS SOFT 22, and the average age of patients was 37.6 ± 5.9, while for the control group it was 39 ± 7.8, and statistically significant differences were found between the two groups with regard to systolic blood pressure. Smoking is an important risk factor for high blood pressure (BP). Smoking increases hypertension temporarily, increasing the risk of blood vessel damage. Continuing to smoke can cause your arteries to narrow and stiffen, and this negative effect may persist even years after stop smoking